Systematic analysis of MADS-box gene family in the U’s triangle species and targeted mutagenesis of BnaAG homologs to explore its role in floral organ identity in Brassica napus - Song, Min; Zhang, Yanfeng; Jia, Qingli; Huang, Shuhua; An, Ran; Chen, Nana; Zhu, Yantao; Mu, Jianxin; Hu, Shengwu (Frontiers in Plant Science, 2023)
MADS-box transcription factors play an important role in regulating floral organ development and participate in environmental responses. To date, the MADS-box gene family has been widely identified in Brassica rapa (B. rapa), Brassica oleracea (B. oleracea), and Brassica napus (B. napus); however, there are no analogous reports in Brassica nigra (B. nigra), Brassica juncea (B. juncea), and Brassica carinata (B. carinata). In this study, a whole-genome survey of the MADS-box gene family was performed for the first time in the triangle of U species, and a total of 1430 MADS-box genes were identified. Based on the phylogenetic relationship and classification of MADS-box genes in Arabidopsis, 1430 MADS-box genes were categorized as M-type subfamily (627 genes), further divided into Mα, Mβ, Mγ, and Mδ subclades, and MIKC-type subfamily (803 genes), further classified into 35 subclades. Gene structure and conserved protein motifs of MIKC-type MADS-box exhibit diversity and specificity among different subclades. Comparative analysis of gene duplication events and syngenic gene pairs among different species indicated that polyploidy is beneficial for MIKC-type gene expansion. Analysis of transcriptome data within diverse tissues and stresses in B. napus showed tissue-specific expression of MIKC-type genes and a broad response to various abiotic stresses, particularly dehydration stress. In addition, four representative floral organ mutants (wtl, feml, aglf-2, and aglf-1) in the T0 generation were generated by editing four BnaAG homoeologs that enriched the floral organ variant phenotype. In brief, this study provides useful information for investigating the function of MADS-box genes and contributes to revealing the regulatory mechanisms of floral organ development in the genetic improvement of new varieties.